1998
DOI: 10.4095/209487
|View full text |Cite
|
Sign up to set email alerts
|

The ice cap of Hoodoo Mountain volcano, northwestern British Columbia: estimates of shape and thickness from surface radar surveys

Abstract: Preliminary results from a multiple-traverse radar survey across an ice cap situated on top of Hoodoo Mountain, a Quaternary subglacial stratovolcano in northwestern British Columbia are presented. The project defined the shape of the ice sheet and mapped the subglacial summit region of the volcano. Four traverses, using low-frequency ice radar and higher frequency ground-penetrating radar units, provided traces of the ice base as well as shallow, finer scale, internal reflectors. GPS was used to locate sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Volcanic stratigraphy is particularly appropriate for study by GPR because the deposits are commonly thin and compositionally homogeneous, and they can be electrically resistive (Stasiuk & Russell 1994;Russell & Stasiuk 1997). The deposits on Thera are also particularly dry and situated well above the water table, which means that there will be little attenuation of the radar signal by pore or surface water.…”
Section: Ground-penetrating Radarmentioning
confidence: 99%
See 2 more Smart Citations
“…Volcanic stratigraphy is particularly appropriate for study by GPR because the deposits are commonly thin and compositionally homogeneous, and they can be electrically resistive (Stasiuk & Russell 1994;Russell & Stasiuk 1997). The deposits on Thera are also particularly dry and situated well above the water table, which means that there will be little attenuation of the radar signal by pore or surface water.…”
Section: Ground-penetrating Radarmentioning
confidence: 99%
“…The deposits on Thera are also particularly dry and situated well above the water table, which means that there will be little attenuation of the radar signal by pore or surface water. Previous studies by McCoy et al (1992), Stasiuk & Russell (1994), Gilbert et al (1996), Russell & Stasiuk (1997) and Russell et al (1998) have shown that GPR has tremendous potential for quantifying distributions, thicknesses and volumes of volcanic deposits, and perhaps can even be used to study facies variations within individual units.…”
Section: Ground-penetrating Radarmentioning
confidence: 99%
See 1 more Smart Citation